2018
DOI: 10.1107/s2052252517016633
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale structures across the morphotropic phase boundary in PbZr1−x Ti x O3

Abstract: Lead zirconate titanate (PZT) is one of the most widely studied piezoelectric materials, mainly because of its 'mysterious' relationship between the so-called morphotropic phase boundary (MPB) and its strong piezoelectric coupling factor. Using results from a pair distribution function analysis, this paper examines how the complex local structure in PZT affects the long-range average structure across the MPB. A monoclinic M C type structure is discovered in PZT. A first-order transformation between the monocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…In some respects, this thermally driven R-T phase transformation resembles the compositionally driven one in PbZr 1Àx Ti x O 3 (PZT) at the morphotropic phase boundary (MPB, x ' 0.48;Jaffe et al, 1954Jaffe et al, , 1971. In PZT, the Zr-rich side has been recognized as monoclinic rather than rhombohedral close to the MPB, although recent work has shown that the structure is extremely complex, with mixing of disordered and ordered monoclinic regions (Noheda et al, 1999;Yokota et al, 2009;Zhang et al, 2011Zhang et al, , 2014Zhang et al, , 2018Gorfman et al, 2011). have reported a high-resolution X-ray diffraction study of multi-domain NBT 'single' crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In some respects, this thermally driven R-T phase transformation resembles the compositionally driven one in PbZr 1Àx Ti x O 3 (PZT) at the morphotropic phase boundary (MPB, x ' 0.48;Jaffe et al, 1954Jaffe et al, , 1971. In PZT, the Zr-rich side has been recognized as monoclinic rather than rhombohedral close to the MPB, although recent work has shown that the structure is extremely complex, with mixing of disordered and ordered monoclinic regions (Noheda et al, 1999;Yokota et al, 2009;Zhang et al, 2011Zhang et al, , 2014Zhang et al, , 2018Gorfman et al, 2011). have reported a high-resolution X-ray diffraction study of multi-domain NBT 'single' crystals.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the PZT phase diagram developed by Jaffe et al [2] has been accepted as the basic characterization of the PZT solid solution. However, many reports [3][4][5][6][7][8][9] show that the Jaffe's diagram needs verification. One of the reasons for it is that it was developed on the basis of ceramics only, because PZT crystals growth process has been developed only recently.…”
Section: Introductionmentioning
confidence: 99%
“…The structural phase transitions in the perovskite‐type solid solutions involve complex patterns of cationic displacements and octahedra tilts and/or rotations, which are very complex to characterize only by diffraction experiments due coexistence of different symmetries at short and long scale . The characterization of the complex physical behaviour of these materials requires a technique capable of probing the local structure.…”
Section: Introductionmentioning
confidence: 99%
“…It provides clear evidence of phase transitions at low temperature for disordered substituted perovskites in terms of change in the intensities and positions of the Raman bands . In this regard, various researchers have used Raman spectroscopy to get better information of the structural phase transitions especially in case of morphotropic phase boundary (MPB) . Historically, an MPB in (1‐x)PbZrO 3 ‐xPbTiO 3 (PZT) is referred to as the change in the crystal structure of the ferroelectric material from rhombohedral to tetragonal phase on changing its composition or by application of external pressure .…”
Section: Introductionmentioning
confidence: 99%